USING PICTURE MEDIA TO ENHANCE WRITING ABILITY IN PROCEDURE TEXT - Noviati Noviati; Aswadi Jaya; Fitri Nur Hakiki (Universitas 17 Agustus 1945 Surabaya, 2022)
The objective of this research was to find out whether or not there is any significant difference between the tenth grade students of SMA Sriguna Palembang in learning writing procedure text using picture media technique and those who are not. This research was done through Quasi-Experimental (Quantitative). The sample was chosen by using cluster random sampling and students of X MIPA 3 selected as the sample. The pre-test and post-test were conducted from July to August 2022. The pre-test and post-test were conducted to gain the quantitative data that were in the form of students’ writing scores. The students average score of the experimental group in the post-test was 75, while the students’ average score in the control group was 66. Meanwhile the critical value was 0.05 significance level for one-tailed test with 69 (df) was 1.667 since the obtained was 3.028, it was higher than t-table. The result showed that there is a significant difference of writing scores of the tenth grade students taught through picture media and those ones taught a conventional technique at Sriguna Senior High School of Palembang.